Peran Pengasuh Di Rumah Yatim Arrohman Denpasar Dalam Pembentukan Kemandirian Anak Yatim Piatu - Hayuningtyas, Nadia Sanya; Punia, I Nengah; Nugroho, Wahyu Budi (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT Independence in children can be applied at Yatim Arrohman's House which has one of the roles as a place to facilitate children in activities organized and participate in programs that have been arranged by Yatim Arrohman's House to grow and develop according to their age. The formation of independence in orphans can be analyzed through the sociological study of education. The studies attempts at discuss this roles a caregivers at shaping this independence the orphans or the patterns of care applied by Yatim Arrohman's House. Keywords: Independence, Orphan Arrohman's House, Caregiver Role, Orphans